Factors Influencing Consumers' Willingness to Pay for Pure Honey in Ibadan, Oyo State, Nigeria - A. T. Kareem; T. F. Odusanya; J. O. Isola; A. S. Adisa (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to examine the factors influencing consumers' willingness to pay (WTP) for pure honey in Ibadan, Oyo State, Nigeria using appropriate standard methods of 266 consumers across ten marketplaces. Data collected show that the respondents are predominantly male consumers (60%), within the age group of 31–50 years (50%), with tertiary education attainment (50%) and earn monthly incomes between ₦50,000 and ₦100,000 (45%). Awareness of honey’s health benefits (4.5) was found to be a strong driver of WTP, while product purity (4.7), taste (4.5), and packaging (4.0) were critical attributes influencing purchasing decisions. Market dynamics, including price (4.5) and availability (4.2), played significant roles in shaping consumer preferences. The study concluded that improving consumer awareness through education, enhancing product certification, and optimizing packaging design are key strategies for increasing WTP. The findings contribute to forest economics by providing valuable insights into consumer behavior and offering actionable recommendations for producers, marketers, and policymakers to foster a sustainable honey market in urban settings. Future research could explore similar patterns in other forest-derived products and rural areas.